What drives SMEs to adopt e-commerce? The joint role of testosterone and absorptive capacity - Jiafeng Gu (Asia Pacific Journal of Marketing and Logistics, 2023)
Purpose The study aims to investigate the relationship between chief executive officers' (CEOs') prenatal testosterone exposure, absorptive capacity and e-commerce adoption by small and medium-sized enterprises (SMEs). Design/methodology/approach Based on a study of 1,519 SMEs led by a male CEO in China, the impact of entrepreneur's digital ratio on e-commerce adoption is empirically analyzed through a multivariate logistic model. Findings The results show that the second-to-fourth digit ratio (2D:4D), a reverse measurement of prenatal testosterone exposure, is negatively correlated with the adoption of e-commerce by SMEs. This evidence suggests that CEOs with high prenatal testosterone exposure have a higher probability of adopting e-commerce. In addition, this research indicates a positive correlation between absorptive capacity, which is defined by market innovation, process innovation and marketing innovation, and the adoption of e-commerce by SMEs. Originality/value This research can contribute to the discussion by providing new insights into the antecedents of the adoption of e-commerce in SMEs.